Radio Kalambuko, voices from Uncle Raimundo's pit. (Journal of Parents and Teachers, 2014)
Radio becomes a resource for learning. Radio Kalambuko, in particular, realizes a radio program in direct and it covers interviews, music, stories, news, contests and humor. The article explains in detail in what this project consists, how it is done and other indications to take into account.
Keywords: Radio Kalambuko; radio program; education.